Influence of light sources used in a street lighting for building and operating costs of lighting systems - Terrich, Theodor (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
The paper deals with the design of an optimal variant of a public lighting system. Calculations are processed on a model road in urban areas. Completely new lighting system is proposed on 30-years operational period. The objective is to evaluate the benefits of the application of LED in a confrontation with conventional discharge light sources from technical and economic point of view. The decisive criterion is the economic NPV of the expenditure with regard to the amount of cost entering into the calculation.
Vliv užitých světelných zdrojů ve veřejném osvětlení na stavební a provozní výdaje osvětlovacích soustav
Keywords: Design of public lighting systems; economics operation of the lighting systems; usage of LEDs